Pengaruh Kompetensi Sumber Daya Manusia dan Locus of Control terhadap Kualitas Laporan Keuangan LPD - Sudiarti, Ni Wayan; Juliarsa, Gede (E-Jurnal Akuntansi, 2020)
The purpose of this study to determine the effect of human resource competencies and locus of control on the quality of Institute of Countryside Credit (LPD) financial reports. The population in this study were all LPD of Klungkung Regency. The sample technique in this study using the Slovin formula with purposive sampling, as many as 46 samples. Data collection method used is a survey method by distributing questionnaires and documentation. The number of returned questionnaires was 126 questionnaires. The data analysis technique used is doubled linear regression analysis with SPSS. Based on research results, competence of human resources and locus of control have a positive and significant effect on the quality of financial statements. The results of this study are expected to provide additional insights into knowledge for those who play a role in preparing financial reports so as to achieve success in carrying out their duties. Keywords: Financial Report Quality; Human Resource Competencies; Locus Of Control.